2022
DOI: 10.3892/mco.2022.2533
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA dynamics and response to immunotherapy in colorectal cancer

Abstract: Circulating tumor DNA (ctDNA) is increasingly being investigated as a tool to detect minimal residual disease in resected, stage I-III colorectal cancer. Recent ctDNA studies have indicated that detection of ctDNA following surgery for resectable colorectal cancer confers a significantly higher risk of recurrence than those with negative ctDNA postoperatively. In those with postoperative ctDNA positivity, clearance of minimal residual disease with adjuvant chemotherapy is a positive prognostic indicator. Lastl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this study, patients’ KRAS, NRAS, BRAF, and EGFR-S492R mutation was analyzed through ctDNA, and the result show patients with RAS/BRAF WT ctDNA presented with better mOS and mPFS compared to patients with mutated ctDNA. These findings presented the potential role of ctDNA for colon cancer immunotherapy ( 181 ). However, the reports of ctDNA in the immunotherapy of colon cancer are still limited and ctDNA’s predictive role in immunotherapy needs to be verified by larger clinical studies.…”
Section: Peripheral Blood Biomarkers In Colon Cancer Immunotherapymentioning
confidence: 87%
“…In this study, patients’ KRAS, NRAS, BRAF, and EGFR-S492R mutation was analyzed through ctDNA, and the result show patients with RAS/BRAF WT ctDNA presented with better mOS and mPFS compared to patients with mutated ctDNA. These findings presented the potential role of ctDNA for colon cancer immunotherapy ( 181 ). However, the reports of ctDNA in the immunotherapy of colon cancer are still limited and ctDNA’s predictive role in immunotherapy needs to be verified by larger clinical studies.…”
Section: Peripheral Blood Biomarkers In Colon Cancer Immunotherapymentioning
confidence: 87%
“…Furthermore, it is noteworthy that ctDNA was a more reliable marker for disease activity in this patient than CEA, which remained low throughout the treatment course due to his non-CEA-producing tumor. Early studies have suggested that plasma ctDNA could serve as a dynamic marker of tumor response to immunotherapy in patients with metastatic colorectal cancer that is both MSS and MSI-high [41]. A large, multicenter, prospective, observational study enrolling over 1500 patients with solid tumors is underway to evaluate the clinical utility of serial plasma ctDNA assessments on clinical decision-making inclusive of the continuation/discontinuation or intensification/de-intensification of immunotherapy in these patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an elevation in mSEPT9 levels aligns with tumor progression during immunotherapy. 69 However, it is worth noting that a corresponding investigation specific to HCC is lacking. There remains an unaddressed gap in clinical research pertaining to ctDNA in the context of immune checkpoint blockade therapy for patients with HCC.…”
Section: Clinical Application Of Cell-free Dnamentioning
confidence: 99%
“…The utilization of the methylated SEPTIN9 gene (mSEPT9) is prevalent in colorectal cancer, where a reduction in mSEPT9 levels is established as a sign of a positive tumor response to immunotherapy. Conversely, an elevation in mSEPT9 levels aligns with tumor progression during immunotherapy 69 . However, it is worth noting that a corresponding investigation specific to HCC is lacking.…”
Section: Clinical Application Value Of Cfdnamentioning
confidence: 99%